Continued evolution of H6 avian influenza viruses isolated from farms in China between 2014 and 2018. Issue 4 (10th July 2021) - Cui, Jiaqi; Cui, Pengfei; Shi, Jianzhong; Fan, Weifeng; Xing, Xin; Gu, Wenli; Zhang, Yuancheng; Zhang, Yaping; Zeng, Xianying; Jiang, Yongping; Chen, Pucheng; Yang, Huanliang; et al.
Abstract: H6 avian influenza virus (AIV) is one of the most prevalent AIV subtypes in the world. Our previous studies have demonstrated that H6 AIVs isolated from live poultry markets pose a potential threat to human health. In recent years, increasing number of H6 AIVs has been constantly isolated from poultry farms. In order to understand the biological characteristics of H6 AIVs in the context of farms, here, we analyzed the phylogenetic relationships, antigenicity, replication in mice and receptor binding properties of H6 AIVs isolated from farms in China between 2014 and 2018. Phylogenetic analysis showed that 19 different genotypes were formed among 20 representative H6 viruses. Notably, the internal genes of these H6 viruses exhibited complicated relationships with different subtypes of AIVs worldwide, indicating that these viruses are the products of complex and frequent reassortment events. Antigenic analysis revealed that 13 viruses tested were divided into three antigenic groups. 10 viruses examined could all replicate in the respiratory organs of infected mice without prior adaptation. Receptor binding analysis demonstrated that some of the H6 AIVs bound to both α‐2, 3‐linked glycans (avian‐type receptor) and α‐2, 6‐linked glycans (human‐type receptor), thereby posing a potential threat to human health. Together, these findings revealed the prevalence, complicated genetic evolution, diverse antigenicity, and dual receptor binding specificity of H6 AIVs in the settings of poultry farms, which emphasize the importance to continuously monitor the evolution and biological properties of H6 AIVs in nature.